2005
DOI: 10.1021/la047652b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SiO2/Polystyrene Nanocomposite Particles via Miniemulsion Polymerization

Abstract: The SiO(2)/polystyrene nanocomposite particles were synthesized through miniemulsion polymerization by using sodium lauryl sulfate surfactant (SLS), hexadecane costabilizer in the presence of silica particles coated with methacryloxy(propyl)trimethoxysilane. Core-shell or other interesting morphology composite particles were obtained depending on the size of the silica particles and the surfactant concentration employed. By adjusting these parameters, it was possible to control the size and morphology of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
147
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(151 citation statements)
references
References 38 publications
4
147
0
Order By: Relevance
“…Hybrid nanoparticles can be prepared by miniemulsion polymerization in a two-stage process [68][69][70]: first, a nanoparticle-in-monomer suspension is emulsified in a continuous phase and then the polymerization of the filled submicron-sized monomer droplets is conducted [55]. Hecht et al consider high-pressure homogenizers to be the most suitable device to produce small sizes for particle filled monomer droplets at a high throughput [55].…”
Section: Preparation Of Hybrid Nanoparticlesmentioning
confidence: 99%
“…Hybrid nanoparticles can be prepared by miniemulsion polymerization in a two-stage process [68][69][70]: first, a nanoparticle-in-monomer suspension is emulsified in a continuous phase and then the polymerization of the filled submicron-sized monomer droplets is conducted [55]. Hecht et al consider high-pressure homogenizers to be the most suitable device to produce small sizes for particle filled monomer droplets at a high throughput [55].…”
Section: Preparation Of Hybrid Nanoparticlesmentioning
confidence: 99%
“…Tiarks et al 37 modified the auxiliary protocol of 4VP and synthesized colloidal composite particles with core-shell using miniemulsion polymerization. Subsequently, Wu and coworkers 38 reported a controlled synthesis of silica/PS composite particles with core-shell morphology. In this way, surfactant and cosurfactant are added to increase aggregation efficiency of the silica.…”
Section: Introductionmentioning
confidence: 99%
“…Because the hydroxyl groups of silica particles have strong hydrophilic and can induce aggregations, they are immiscible with organic phase and difficult to react with monomers. To solve this problem, Wu and coworkers 38 used a series of silane coupling agents to hydrophobize the silica particles and found that MPS-modified silica and VTS-modified silica could well disperse in styrene. Wang and coworkers 29 successfully used oleic acid to modify the silica for the first time; Dai and Ma 42 prepared PSsilica core-shell composite particles by one-step emulsion polymerization with a nonionic initiator VA-086; V. Ladmiral et al 43 made the surface modification of silica using an alkoxyamine derivative.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, our group also demonstrated the synthesis of nematic liquid crystalsencapsulated PS nanocapsules. [20] In addition, nanocomposites comprised of polymer nanospheres and carbon nanotubes [21] or inorganic nanoparticles (NPs; SiO 2 , Fe 2 O 3 , and TiO 2 ) [22][23][24] have been synthesized by modified miniemulsion polymerization techniques. However, these techniques still requires the condition optimization to control the nanocomposite composition, shape, and size for higher-efficient optical/electronic applications as well as mass-production.…”
Section: Introductionmentioning
confidence: 99%